RO5126766 attenuates osteoarthritis by inhibiting osteoclastogenesis and protecting chondrocytes through mediating the ERK pathway - Han Wang; Xiwen Yuan; Jie Han; Zuoxing Wu; Zheru Ma; Fan Shi; Zhengqiong Luo; Zihan Chen; Chenyang Guo; Guixin Yuan; Xuemei He; Zemin Ling; et al. (Journal of Orthopaedic Translation)
Background: Osteoarthritis (OA) is a degenerative joint disease that remains challenging to treat due to lack of complete understanding of its pathogenesis. Previous studies have identified RO5126766 (RO) as a small molecule compound that inhibited RAF/MEK-ERK pathway and garnered much interest for its anti-cancer properties. But its role in the treatment of OA remains unclear. Methods: This study employed the anterior cruciate ligament transection (ACLT) procedure to create an OA model in mice. The effects of RO on pathological changes in articular cartilage and subchondral bone were assessed using micro-CT and histological staining. Mice received peritoneal injections of RO at 1 mg/kg and 5 mg/kg biweekly for 4 weeks after ACLT, while control mice received saline. In vitro, bone marrow-derived macrophages were cultured to examine the effects of RO on osteoclast activation using immunofluorescence, TRAP staining, and bone resorption assays. The inflammatory degeneration of chondrocytes and gene expression levels were evaluated using staining and RT-qPCR. Western blot and immunohistochemistry were used to analyze MAPK signaling and autophagy-related protein expression, investigating RO's molecular mechanism in OA treatment. Human single-cell data were also analyzed to identify genes and pathways upregulated in OA tissues. Results: Our findings showed that RO protects subchondral bone by inhibiting osteoclast formation in the ACLT mouse model of OA. In vitro, RO was shown to inhibit osteoclast differentiation and reduce inflammatory degeneration of chondrocytes. Mechanistically, RO counteracted subchondral osteoclast hyperactivation by suppressing the ERK/c-fos/NFATc1 signaling pathway. Additionally, RO inhibited LPS-induced inflammatory degeneration of chondrocytes and enhanced autophagy via the ERK pathway. Single-cell analysis further confirmed significant upregulation of the ERK signaling pathway in human OA tissues. Conclusions: Overall, our findings suggested that RO inhibited osteoclast differentiation and protected articular cartilage, suggesting its potential as a novel treatment for OA. Translational potential of this article: In this study, we have, for the first time, substantiated the therapeutic potential of RO in the treatment of OA. By demonstrating its ability to inhibit osteoclast differentiation and protect articular cartilage, RO could offer a new avenue for disease-modifying treatments in OA. Thus, this paper provides valuable insights into understanding the molecular mechanisms and treatment of OA.